Effects of Surrounding Information and Line Length on Text Comprehension from the Web - Jess McMullin; Connie K. Varnhagen; Pheng Heng; Xornam Apedoe (The Canadian Network for Innovation in Education (CNIE), 2002)
The World Wide Web (Web) is becoming a popular medium for transmission of information and online learning. We need to understand how people comprehend information from the Web to design Web sites that maximize the acquisition of information. We examined two features of Web page design that are easily modified by developers, namely line length and the amount of surrounding information, or whitespace. Undergraduate university student participants read text and answered comprehension questions on the Web. Comprehension was affected by whitespace; participants had better comprehension for information surrounded by whitespace than for information surrounded by meaningless information. Participants were not affected by line length. These findings demonstrate that reading from the Web is not the same as reading print and have implications for instructional Web design.